Functional current collector, pole piece using same and battery

By using magnetron sputtering on the surface of the substrate in the battery and plating a second copper layer on its surface, the problems of low energy density and high cost caused by traditional copper foil current collectors are solved, and the energy density of the battery and the safety performance are enhanced.

CN119742372AActive Publication Date: 2025-04-01JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD

Patent Information

Application Number
CN202411923455.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing batteries that use traditional copper foil as the negative electrode current collector have problems of low energy density and high battery cost.

Method used

A functional current collector including a substrate and a first copper layer prepared by magnetron sputtering process on the surface of the substrate is adopted. The X-ray diffraction peak intensity ratio at the crystal surfaces of the first copper layer is controlled at 6≤I(111)/I(200)≤8, and a second copper layer is plated on the surface thereof.

Benefits of technology

The energy density of the battery is improved, the battery cost is reduced, and the battery safety performance and cycle life are improved by reducing the recrystallization time and defects of the copper layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742372A_ABST
    Figure CN119742372A_ABST
Patent Text Reader

Abstract

The invention provides a functional current collector, a pole piece using the same and a battery. The functional current collector comprises a base material and a first copper layer and a second copper layer which are sequentially arranged on at least one surface of the base material, the first copper layer is prepared through a magnetron sputtering process, the second copper layer is prepared through an electroplating process, and the X-ray diffraction peak intensity I (111) of the first copper layer on a crystal face (111) and the X-ray diffraction peak intensity I (200) of the first copper layer on a crystal face (200) meet the condition that I (111) / I (200) is larger than or equal to 6 and smaller than or equal to 8. The first copper layer of the functional current collector provided by the invention satisfies 6 < = I (111) / I (200) < = 8, so that the defects of dislocation, interface and the like during molding caused by grain growth and thermal deformation when the second copper layer is compounded on the surface of the first copper layer can be improved, the defects of the second copper layer are reduced, the compactness is higher, the resistivity of the functional current collector is reduced, and the service life of the functional current collector is prolonged. And the energy density, the cycle life and the safety performance of the battery using the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a functional current collector, a pole piece and a battery using the functional current collector. Background Art

[0002] With the rapid development of new energy and electronic technology, the cycle life, safety performance, energy density, etc. of batteries have become top priorities. As a very important part of the battery, the current collector is used to collect the current generated by the active materials of the battery in order to form a larger current output. Its performance will directly affect the cycle life, energy density, safety performance, etc. of the battery.

[0003] Currently, the negative electrode sheets in lithium batteries and sodium batteries mostly use copper foil as the current collector. This type of current collector has high cost and quality, which is not conducive to controlling battery costs and improving energy density. Summary of the invention

[0004] In order to solve the problems of low energy density and high battery cost in existing batteries using traditional copper foil as negative electrode current collector, the present invention provides a functional current collector, a pole piece and a battery using the same.

[0005] According to a first aspect of the present invention, a functional current collector is provided, the functional current collector comprising a substrate and a first copper layer disposed on at least one surface of the substrate, the first copper layer being prepared by a magnetron sputtering process, and the X-ray diffraction peak intensity of the first copper layer at the (111) crystal plane being I (111) , the X-ray diffraction peak intensity of the first copper layer at the (200) crystal plane is I (200) , I (111) ,I (200) Satisfied, 6≤I (111) / I (200) ≤8.

[0006] Compared with traditional copper foil, the inner layer of the functional current collector provided by the present invention is a substrate, and at least one side is a copper layer. The functional current collector provided by the present invention is applied to pole pieces and batteries. On the one hand, it can improve the energy density of the battery and reduce the battery cost. On the other hand, when thermal runaway occurs in the battery, the copper layer on the surface of the functional current collector is more easily disconnected, thereby isolating the connection between the active material and the functional current collector, effectively preventing the continuation of thermal runaway of the battery and improving the safety performance of the battery.

[0007] The current parameters, plating solution concentration, plating time and other parameters of the functional current collector during the electroplating process do not regularly affect the recrystallization time and recrystallization quality of the metal layer of the functional current collector, so it is difficult to control the recrystallization time through the preparation process parameters of the functional current collector. The metal coating on the functional current collector has a face-centered cubic structure with crystal plane diffraction peaks such as (111), (200), (220) and (311). The inventors of the present application have found that the recrystallization time and quality of the metal layer in the functional current collector are closely related to the ratio of the crystal plane orientation of the metal layer at (111) and (200).

[0008] Based on the above findings, the present invention obtains a first copper layer by magnetron sputtering on the surface of the substrate of the functional current collector. The X-ray diffraction peak intensity I (111) The X-ray diffraction peak intensity I (200) The ratio I (111) / I (200) The invention is controlled within the range of 6 to 8. Firstly, when the second copper layer is plated on the surface of the first copper layer by the electroplating process, the recrystallization time of the second copper layer in the surface composite process of the first copper layer during the electroplating process can be reduced, thereby reducing the production cycle of the functional current collector, the storage cost and the time cost related to the product cycle of the functional current collector; secondly, the defects such as dislocation and interface generated during the molding process due to grain growth and thermal deformation when the second copper layer is composited on the surface of the first copper layer are improved, so that the defects of the second copper layer obtained by the electroplating process are reduced and the density is higher, which can improve the reliability of the functional current collector, thereby improving the safety performance of the battery using the functional current collector; thirdly, the reduction of defects in the second copper layer can improve the quality of the metal layer, thereby improving the strength and quality of the functional current collector, reducing the resistivity of the functional current collector, thereby improving the energy density of the battery using the functional current collector, and at the same time reducing the risk of the copper layer falling off when the functional current collector is used in the battery, thereby significantly improving the cycle life and safety performance of the battery using the functional current collector.

[0009] If the X-ray diffraction peak intensity I (111) The X-ray diffraction peak intensity I (200) The ratio I (111) / I (200) >8, the recrystallization time of the second copper layer during the process of being compounded on the surface of the first copper layer will increase, which will reduce the recrystallization quality of the second copper layer, increase the defects of the second copper layer, and further increase the resistivity of the functional current collector; if the X-ray diffraction peak intensity I of the first copper layer on the surface of the substrate of the functional current collector at the (111) crystal plane (111) The X-ray diffraction peak intensity I (200)The ratio I (111) / I (200) <6, during the surface recrystallization process of the second copper layer on the first copper layer, the recrystallization time of the second copper layer will increase and the recrystallization quality of the second copper layer will decrease, resulting in an increase in defects in the second copper layer, thereby increasing the resistivity of the functional current collector.

[0010] Preferably, 6.2≤I (111) / I (200) ≤7.7.

[0011] Preferably, 6.2≤I (111) / I (200) ≤7.5.

[0012] The X-ray diffraction peak intensity I of the first copper layer on the surface of the substrate of the functional current collector at the (111) crystal plane is further calculated. (111) The X-ray diffraction peak intensity I (200) The ratio I (111) / I (200) By controlling the resistivity within the range of 6.2 to 7.5, the resistivity of the functional current collector can be further reduced, so that the cycle energy density of the battery using the functional current collector can be further improved.

[0013] Preferably, the thickness of the first copper layer is 30-80 nm.

[0014] Preferably, the thickness of the second copper layer is 0.5-2 μm.

[0015] Preferably, the substrate is selected from at least one of polyethylene terephthalate (PET) film, polypropylene (PP) film, and polyimide (PI) film.

[0016] Preferably, the thickness of the substrate is 3-10 μm.

[0017] The thickness of the first copper layer sequentially compounded on the two surfaces of the current collector substrate is controlled within the range of 30 to 80 nm, the thickness of the second copper layer is controlled within the range of 0.5 to 2 μm, and the thickness of the substrate is controlled within the range of 3 to 10 μm. The functional current collector has a thinner metal layer on the surface and a lighter internal polymer substrate, which can greatly reduce the overall weight of the functional current collector, thereby improving the energy density of the battery using the functional current collector.

[0018] According to a second aspect of the present invention, a method for preparing a functional current collector is provided, comprising the following steps: utilizing a magnetron sputtering process to plate a first copper layer on at least one surface of a substrate, and utilizing an electroplating process to plate a second copper layer on the surface of the first copper layer to obtain a functional current collector; in the magnetron sputtering process, controlling the substrate bias voltage within the range of -(185 to 265) V, the power being 12 to 16 kW, and the argon gas flow rate being 40 to 80 sccm.

[0019] The first copper layer and the second copper layer are deposited on the surface of the substrate by magnetron sputtering and electroplating, respectively. During the formation process of compounding the second copper layer on the surface of the first copper layer by electroplating, the second copper layer will undergo a recrystallization process due to self-repair of microscopic defects.

[0020] In the preparation method of the functional current collector provided in the present invention, a first copper layer is composited on at least one surface of a substrate by a magnetron sputtering process, and the substrate bias voltage of the magnetron sputtering is controlled within the range of -265V to -185V, while the power is controlled between 12 and 16kW, and the argon gas flow rate is between 40 and 80sccm, so that the X-ray diffraction peak intensity I of the first copper layer on the surface of the substrate of the final functional current collector at the (111) crystal plane is (111) The X-ray diffraction peak intensity I (200) The ratio satisfies 6≤I (111) / I (200) ≤8, which can effectively improve the compactness of the second copper layer obtained after electroplating, reduce the resistivity of the functional current collector, and thus improve the energy density and safety performance of the battery using the functional current collector.

[0021] According to a third aspect of the present invention, a pole piece is provided, which comprises the above-mentioned functional current collector or a functional current collector prepared by the above-mentioned method for preparing the functional current collector.

[0022] According to a fourth aspect of the present invention, a battery is provided, comprising the above-mentioned electrode sheet.

[0023] The functional current collector provided by the present invention is applied to pole pieces and batteries, which can give the batteries excellent energy density, cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic structural diagram of the functional current collector provided by the present invention.

[0025] The reference numerals are: 1 substrate, 2 first copper layer, 3 second copper layer. DETAILED DESCRIPTION

[0026] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] A functional current collector having a structure such as Figure 1 As shown, the functional current collector includes a substrate 1 and a first copper layer 2 and a second copper layer 3 sequentially arranged on two surfaces of the substrate 1, wherein the substrate 1 is a polypropylene (PP) film;

[0029] The functional current collector provided in this embodiment is prepared by the following steps:

[0030] S1. Equipment preparation

[0031] Prepare a high vacuum winding magnetron sputtering equipment to ensure that the equipment operates normally, and prepare an electroplating line to ensure that it can operate normally;

[0032] S2. Target preparation

[0033] Choose copper with a smooth surface and no impurities as the target material;

[0034] S3. Substrate Preparation

[0035] A PP film with a thickness of 4.5 μm and a smooth surface without impurities is selected as substrate 1;

[0036] S4. Magnetron sputtering

[0037] Start the magnetron sputtering device, control the substrate bias voltage of the magnetron sputtering device to -225V, the power to 14kW, the argon gas flow rate to 60sccm, the winding coating speed to 5m / min, and plate a first copper layer 2 with a thickness of 60nm on both surfaces of the PP film;

[0038] S5. Electroplating

[0039] The second copper layer 3 with a thickness of 1 μm is plated on the surface of the first copper layer 2 by an electroplating process to obtain the functional current collector of this embodiment.

[0040] Example 2

[0041] This embodiment provides a functional current collector, and compared with the embodiment 1, the difference in structure is that in the preparation step S4 of the functional current collector, the substrate bias voltage of the magnetron sputtering device is controlled to be -185 V. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0042] Example 3

[0043] This embodiment provides a functional current collector, and compared with the embodiment 1, the difference in structure is that in the preparation step S4 of the functional current collector, the substrate bias of the magnetron sputtering device is controlled to be -265 V. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0044] Example 4

[0045] This embodiment provides a functional current collector, and compared with embodiment 1, the difference in structure is that in step S4 of preparing the functional current collector, the power of the magnetron sputtering device is controlled to be 16 kW. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0046] Example 5

[0047] This embodiment provides a functional current collector, and compared with embodiment 1, the difference in structure is that in step S4 of preparing the functional current collector, the power of the magnetron sputtering device is controlled to be 12 kW. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0048] Example 6

[0049] This embodiment provides a functional current collector, and compared with the embodiment 1, the difference in structure is that in the functional current collector preparation step S4, the argon gas flow rate is controlled to be 80 sccm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0050] Example 7

[0051] This embodiment provides a functional current collector, and compared with the embodiment 1, the difference in structure is that in the functional current collector preparation step S4, the argon gas flow rate is controlled to be 40 sccm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0052] Comparative Example 1

[0053] This comparative example provides a functional current collector. Compared with Example 1, the difference in structure is that in the preparation step S4 of the functional current collector, the substrate bias voltage of the magnetron sputtering device is controlled to be -115V, the power is 18kW, and the argon gas flow rate is 30sccm. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0054] Comparative Example 2

[0055] This comparative example provides a functional current collector. Compared with Example 1, the difference in structure is that in the preparation step S4 of the functional current collector, the substrate bias voltage of the magnetron sputtering device is controlled to be -325V, the power is 10kW, and the argon gas flow rate is 90sccm. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0056] Test Case

[0057] 1. Participants

[0058] In this test example, the functional current collectors prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were used as test objects to conduct relevant performance tests.

[0059] 2. Test content

[0060] (1) Crystal plane orientation

[0061] The "crystal plane orientation" described in this test example refers to the X-ray diffraction peak intensity of the first copper layer obtained by magnetron sputtering in the functional current collector at different crystal planes, that is, the integrated area of ​​the X-ray diffraction peak, with the X-ray diffraction peak intensity of the first copper layer obtained by magnetron sputtering at the (111) crystal plane as I (111) The X-ray diffraction peak intensity at the (200) crystal plane is I (200) The diffraction angle and diffraction intensity of the crystal of the first copper layer to X-rays are measured by X-ray crystal diffraction. Different crystal planes will produce specific diffraction peaks. The crystal plane orientation of the first copper layer can be analyzed according to the position and intensity of the diffraction peaks. The lattice parameters and crystal plane orientation of the crystal can be determined by the above diffraction angle and diffraction intensity, and then I (111) and I (200) and the ratio of the two.

[0062] (2) Resistivity

[0063] The resistivity of the functional current collector was tested using a BEST-300C automatic four-probe resistivity tester (purchased from Beijing Beiguang Precision Instrument Co., Ltd.). The resistivity changes with time during the recrystallization process of the copper layer. After the electroplating is completed and allowed to stand for 30 minutes, the resistivity is tested every 6 minutes until the resistivity is measured for 10 consecutive times and does not change. The resistivity is the resistivity after the recrystallization is completed, that is, the final resistivity measured.

[0064] The resistivity of the functional current collector indirectly reflects the energy density and safety performance of the battery using the functional current collector. Specifically, first, during the battery charging and discharging process, the resistivity is low and the transmission loss of electric energy is reduced, which enables more electric energy to be effectively stored and released, thereby increasing the actual available energy of the battery. The lower resistivity helps to reduce the ohmic polarization inside the battery, reduce the heat generated by the internal resistance of the battery, and improve the charging and discharging efficiency of the battery. This means that at the same volume and weight, the battery can store and release more electric energy, thereby increasing the energy density. That is, the lower the resistivity of the functional current collector, the higher the energy density of the battery using the functional current collector. Second, the second copper layer of the functional current collector has a short recrystallization time and a low resistivity, indicating that the recrystallization quality of the second copper layer is very good. The good quality of the second copper layer can reduce the risk of peeling and falling off of the second copper layer, and the relative stress will also be reduced, thereby improving the safety performance of the functional current collector.

[0065] (3) Recrystallization time

[0066] The resistivity of the material (the second copper layer of the functional current collector) will also change during the recrystallization process. After the electroplating is completed and the resistivity is left to stand for 30 minutes, the resistivity is tested every 6 minutes until the resistivity is measured for 10 consecutive times and no longer changes. The first measurement time among the 10 consecutive times without change is taken as the end time of recrystallization. The time difference between the first measurement time and the time when the electroplating is completed is the recrystallization time of the second copper layer.

[0067] 3. Experimental results

[0068] Table 1. Test results of relevant performance of functional fluid collectors

[0069]

[0070] The relevant performance test results of the functional collector are shown in Table 1.

[0071] The functional current collectors prepared in Examples 1 to 7 and Comparative Examples 1 to 2 all include a substrate and copper layers disposed on both surfaces of the substrate, except that the first copper layer of the functional current collector prepared in Comparative Example 1 has an X-ray diffraction peak intensity I at the (111) crystal plane. (111) The X-ray diffraction peak intensity I (200) The ratio I (111) / I (200) <6, the X-ray diffraction peak intensity I of the first copper layer of the functional current collector prepared in Comparative Example 2 at the (111) crystal plane (111) The X-ray diffraction peak intensity I (200) The ratio I (111) / I (200)>8, while the X-ray diffraction peak intensity I of the first copper layer of the functional current collector prepared in Examples 1 to 7 at the (111) crystal plane is (111) The X-ray diffraction peak intensity I (200) The ratio satisfies 6≤I (111) / I (200) ≤8.

[0072] Compared with Comparative Examples 1-2, the recrystallization time of the second copper layer in the functional current collector of Examples 1-7 during the preparation process is between 2.6 and 3.5 h, which is shorter than that of Comparative Examples 1-2. The resistivity of the functional current collector prepared in Examples 1-7 is between (2.65 and 3.53)×10 -8 Ω·m, which is significantly lower than that of Comparative Examples 1 to 2. The reason for the above phenomenon is that in the preparation process of the functional current collectors in Examples 1 to 7, the substrate bias voltage of the magnetron sputtering is controlled within the range of -265V to -185V, so that the X-ray diffraction peak intensity I of the first copper layer on the surface of the substrate of the final functional current collector at the (111) crystal plane is (111) The X-ray diffraction peak intensity I (200) The ratio satisfies 6≤I (111) / I (200) ≤8, can not only reduce the recrystallization time of the second copper layer in the process of being compounded on the surface of the first copper layer during electroplating, but also improve the defects such as dislocation and interface caused by grain growth and thermal deformation during the molding process when the second copper layer is compounded on the surface of the first copper layer, so that the defects of the second copper layer obtained by the electroplating process are reduced and the density is higher, and the resistivity of the functional current collector is reduced; while the substrate bias voltage of magnetron sputtering in the preparation process of the functional current collector of comparative examples 1 to 2 is not within the range of -265 to -185V, and the X-ray diffraction peak intensity I of the first copper layer on the surface of the substrate of the finally obtained functional current collector at the (111) crystal plane (111) The X-ray diffraction peak intensity I (200) The ratio does not satisfy 6≤I (111) / I (200) ≤8, the recrystallization time will increase during the process of the second copper layer being composited on the surface of the first copper layer, and the defects in the second copper layer forming process will increase, so that the resistivity of the functional current collector will increase significantly, and the energy density of the battery using the functional current collectors of Comparative Examples 1 to 2 will decrease significantly.

[0073] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A functional current collector, characterized in that: The functional current collector comprises a substrate and a first copper layer and a second copper layer sequentially arranged on at least one surface of the substrate, wherein the first copper layer is prepared by a magnetron sputtering process, and the second copper layer is prepared by an electroplating process; The X-ray diffraction peak intensity of the first copper layer at the (111) crystal plane is I (111) , the X-ray diffraction peak intensity of the first copper layer at the (200) crystal plane is I (200) , the I (111) , said I (200) Satisfied, 6≤I (111) / I (200) ≤8.

2. The functional fluid collector according to claim 1, characterized in that: 6.2≤I (111) / I (200) ≤7.7。 3. The functional fluid collector according to claim 1, characterized in that: 6.2≤I (111) / I (200) ≤7.5。 4. The functional fluid collector according to claim 1, characterized in that: The thickness of the first copper layer is 30-80 nm.

5. The functional fluid collector according to claim 1, characterized in that: The thickness of the second copper layer is 0.5-2 μm.

6. The functional current collector according to claim 1, characterized in that: The substrate is selected from at least one of a polyethylene terephthalate film, a polypropylene film, and a polyimide film.

7. The functional fluid collector according to claim 1, characterized in that: The thickness of the substrate is 3-10 μm.

8. A method for preparing a functional current collector, characterized in that: The following steps are involved: Plating a first copper layer on at least one surface of the substrate by a magnetron sputtering process, and plating a second copper layer on the surface of the first copper layer by an electroplating process to obtain the functional current collector; In the magnetron sputtering process, the substrate bias voltage is controlled within the range of -(185-265) V, the power is 12-16 kW, and the argon gas flow rate is 40-80 sccm.

9. A pole piece, characterized in that: The pole piece includes the functional current collector according to any one of claims 1 to 7 or a functional current collector prepared by the method for preparing the functional current collector according to claim 8.

10. A battery, characterized in that: The battery comprises the electrode piece as claimed in claim 9.

Citation Information

Patent Citations

  • Composite copper foil current collector and preparation method thereof

    CN117117203A

  • Composite copper foil current collector and preparation method and production system thereof

    CN117497687A

  • Composite copper foil, preparation method thereof and lithium ion secondary battery

    CN117712386A

  • Composite current collector and pole piece and secondary battery applying same

    CN118943377A

  • Composite current collector and preparation method thereof

    CN119040832A

Cited By

  • Composite current collector and preparation method thereof, lithium metal battery and electric equipment

    CN120933382A